Indication of common bean cultivars based in joint evaluation of different growing seasons - Pereira, Helton Santos; Melo, Leonardo Cunha; Faria, Luís Cláudio de; Del Peloso, Maria José; Díaz, José Luís Cabrera; Wendland, Adriane (Pesquisa Agropecuaria Brasileira, 2011)
The objectives of this work were to verify the genotype x growing seasons interaction in common beans, to evaluate the importance of the complex interaction and to verify the need to indicate cultivars for each growing season, in a region of intermediate altitude of Paraná and Santa Catarina states, Brazil. Grain yield data of 16 genotypes in 12 trials carried out in two growing seasons were used. Variance analysis was performed with the decomposition of genotype x environments interaction. The percentage of complex interaction was estimated between pairs of environments and also by the Spearman correlations between the growing seasons, using genotype's grain yield means and stability parameters obtained from Annicchiarico's methodology. Differences among growing seasons and genotype x growing season's interaction were detected; however, with lower importance than others double interactions with genotypes. The Spearman correlations between growing seasons showed that genotype x growing season's interaction is predominantly simple. The complex percentage mean of genotypes x growing season's interaction between pairs of environments showed that the alteration of classification is the same between pairs of a same growing season or between pairs of different growing seasons. It is not necessary to indicate common beans cultivars to each growing season, in the studied region.